2016
DOI: 10.1007/s11356-016-6842-7
|View full text |Cite
|
Sign up to set email alerts
|

Sequential use of the STICS crop model and of the MACRO pesticide fate model to simulate pesticides leaching in cropping systems

Abstract: The current challenge in sustainable agriculture is to introduce new cropping systems to reduce pesticides use in order to reduce ground and surface water contamination. However, it is difficult to carry out in situ experiments to assess the environmental impacts of pesticide use for all possible combinations of climate, crop, and soils; therefore, in silico tools are necessary. The objective of this work was to assess pesticides leaching in cropping systems coupling the performances of a crop model (STICS) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
3
2

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 39 publications
0
6
0
1
Order By: Relevance
“…• urban and peri-urban production systems to feed ever-expanding cities, operating in highly constrained conditions with a generally excessive and inappropriate use of chemical and organic inputs� In terms of LCA modelling, tropical contexts generate specific issues� Most existing direct emission models used in LCA were calibrated for field conditions of crops growing in temperate environments (practices, soil characteristics, temperature, rainfall, etc�)� Hence, their validity domain pertains to the conditions for which they were initially calibrated� It is notably true for the Swiss model suite SALCA (Swiss Agricultural LCA) used in ecoinvent, which encompasses the modelling of all primary field emissions, e�g� nitrogen, phosphorus and trace element emissions, while relying on field data collected in Switzerland only� Other commonly used empirical models for nitrogen and carbon compounds are the IPCC guidelines (IPCC 2006, Volume 4, Chapter 11)� These guidelines are regularly updated to account for state of the art� For instance, in the latest version (IPCC 2019), models from Stehfest and Bouwman (2006) or Cardinael et al (2018) were updated� But the coverage of tropical conditions in the background datasets is still limited (Bouwman et al 2002c)� Existing direct field emission models were not designed -or calibrated -to properly consider specific tropical conditions nor developing and emerging contexts, i�e� the pedoclimatic conditions or the substantial variability in practices (e�g� the high diversity of field inputs, agroforestry systems, etc�) (Table 6�1, more details in Appendix B p� 122)� This issue was also recently demonstrated for pesticide emission models by Gentil et al (2019) and for N emission models by Avadí et al (2022)� Other process-based models exist, such as APSIM (Holzworth et al 2018), STICS (Brisson et al 2003) and combinations of models (Constantin et al 2015;Lammoglia et al 2017), that make it possible to calibrate the models to very specific site conditions� However, calibrating process-based models requires specific expertise and extensive datasets� Moreover, such models are not available for all cropping systems, nor can all process-based models model the field emissions in a mechanistic way� The same limitations apply to impact assessment models which are either too generic or valid only for temperate conditions� For instance, Gentil et al (2019) highlighted in their review the lack of validity of ecotoxicity data for tropical species that show a specific sensitivity to the exposure to pollutants� Avadí et al (2022) demonstrated that direct field nitrogen emissions modelling is to date not well adapted to tropical conditions, organic fertilization, or short-cycle crops such as market vegetables�…”
Section: Diversity Of Agri-food Systems Due To Specific Natural Conditions and Combined Socio-economic Constraintsmentioning
confidence: 92%
“…• urban and peri-urban production systems to feed ever-expanding cities, operating in highly constrained conditions with a generally excessive and inappropriate use of chemical and organic inputs� In terms of LCA modelling, tropical contexts generate specific issues� Most existing direct emission models used in LCA were calibrated for field conditions of crops growing in temperate environments (practices, soil characteristics, temperature, rainfall, etc�)� Hence, their validity domain pertains to the conditions for which they were initially calibrated� It is notably true for the Swiss model suite SALCA (Swiss Agricultural LCA) used in ecoinvent, which encompasses the modelling of all primary field emissions, e�g� nitrogen, phosphorus and trace element emissions, while relying on field data collected in Switzerland only� Other commonly used empirical models for nitrogen and carbon compounds are the IPCC guidelines (IPCC 2006, Volume 4, Chapter 11)� These guidelines are regularly updated to account for state of the art� For instance, in the latest version (IPCC 2019), models from Stehfest and Bouwman (2006) or Cardinael et al (2018) were updated� But the coverage of tropical conditions in the background datasets is still limited (Bouwman et al 2002c)� Existing direct field emission models were not designed -or calibrated -to properly consider specific tropical conditions nor developing and emerging contexts, i�e� the pedoclimatic conditions or the substantial variability in practices (e�g� the high diversity of field inputs, agroforestry systems, etc�) (Table 6�1, more details in Appendix B p� 122)� This issue was also recently demonstrated for pesticide emission models by Gentil et al (2019) and for N emission models by Avadí et al (2022)� Other process-based models exist, such as APSIM (Holzworth et al 2018), STICS (Brisson et al 2003) and combinations of models (Constantin et al 2015;Lammoglia et al 2017), that make it possible to calibrate the models to very specific site conditions� However, calibrating process-based models requires specific expertise and extensive datasets� Moreover, such models are not available for all cropping systems, nor can all process-based models model the field emissions in a mechanistic way� The same limitations apply to impact assessment models which are either too generic or valid only for temperate conditions� For instance, Gentil et al (2019) highlighted in their review the lack of validity of ecotoxicity data for tropical species that show a specific sensitivity to the exposure to pollutants� Avadí et al (2022) demonstrated that direct field nitrogen emissions modelling is to date not well adapted to tropical conditions, organic fertilization, or short-cycle crops such as market vegetables�…”
Section: Diversity Of Agri-food Systems Due To Specific Natural Conditions and Combined Socio-economic Constraintsmentioning
confidence: 92%
“…Conservation agriculture generally refers to a farming approach built on three main principles: It is important to note that, while conservation agriculture generates a number of benefits, it most often makes use of herbicides to manage weeds, which has detrimental effects on soil biodiversity, water quality and farmers health (Lammoglia et al, 2017). Furthermore, the contribution to mitigating climate change, through accumulation of organic C in soil, has sometimes been overstated.…”
Section: Conservation Agriculturementioning
confidence: 99%
“…Es importante señalar que, si bien la agricultura de conservación genera una serie de beneficios, en la mayoría de los casos, hace uso de herbicidas para controlar las malas hierbas, lo que tiene efectos perjudiciales sobre la biodiversidad del suelo, la calidad del agua y la salud de los agricultores (Lammoglia et al, 2017). Además, su contribución a mitigar el cambio climático, a través de la acumulación de C orgánico en el suelo, a veces ha sido exagerada.…”
Section: Agricultura De Conservaciónunclassified